The Impact of Intellectual Capital on Entrepreneurship for Saudi Telecom Companies - Marai, Khaikan Fawaz Abdel Hamid; Hassan, Hanan Osama (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to analyze the impact of intellectual capital dimensions in achieving the entrepreneurship of Saudi Telecom companies and the availability of intellectual capital requirements.The data was collected via a questionnaire that was distributed to all telecom companies (Zain, Mobily and STC) in Tabuk region. Field survey was selected and 150 questionnaires were distributed, of which 121 were collectedi.e, 80.7%, which is appropriate for research purposes via the analytical descriptive approach.The study came out with a number of results, prominently the increased tendency of the telecom companies in Tabuk towards the dimensions of intellectual capital. Preservation, of intellectual capital was ranked first, while enhancing customer interest and service was ranked last.Moreover, it was found that there is a significant positive relationship between intellectual capital and entrepreneurship.
Keywords: Intellectual Capital; Entrepreneurship; Telecom Sector; Tabuk